2020
DOI: 10.3390/antibiotics9090564
|View full text |Cite
|
Sign up to set email alerts
|

Phages as a Cohesive Prophylactic and Therapeutic Approach in Aquaculture Systems

Abstract: Facing antibiotic resistance has provoked a continuously growing focus on phage therapy. Although the greatest emphasis has always been placed on phage treatment in humans, behind phage application lies a complex approach that can be usefully adopted by the food industry, from hatcheries and croplands to ready-to-eat products. Such diverse businesses require an efficient method for combating highly pathogenic bacteria since antibiotic resistance concerns every aspect of human life. Despite the vast abundance o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 119 publications
(169 reference statements)
0
16
0
Order By: Relevance
“…The aqueous environment of the urinary tract makes it a convenient niche for therapeutic applications. Water favors multidirectional motion of phage particles and increases the possibility of contact between them and their bacterial hosts [ 56 ], whereas a low-moisture environment significantly reduces phage mobility and, indirectly, their lytic action. Phages deprived of mobility are unable to attach to specific receptors on bacterial surface, which results in an inability to disrupt the bacterial cell wall and initiate the infection [ 57 ].…”
Section: Phages In the Development And Treatment Of Utismentioning
confidence: 99%
“…The aqueous environment of the urinary tract makes it a convenient niche for therapeutic applications. Water favors multidirectional motion of phage particles and increases the possibility of contact between them and their bacterial hosts [ 56 ], whereas a low-moisture environment significantly reduces phage mobility and, indirectly, their lytic action. Phages deprived of mobility are unable to attach to specific receptors on bacterial surface, which results in an inability to disrupt the bacterial cell wall and initiate the infection [ 57 ].…”
Section: Phages In the Development And Treatment Of Utismentioning
confidence: 99%
“…Less attention has been paid to the opportunity to use phages as biocontrol agents in the environment ( 27 ). Yet, increasingly, phages are being used in other industries such as for medical devices ( 28 ), agriculture ( 29 ), aquaculture ( 29 31 ), and the food industry ( 29 , 32 ) as prophylactic treatments to prevent disease. However, challenges remain in the widespread implementation of phage treatments, including the development of phage resistance, regulation of phage-based products, and unknown environmental consequences of phage treatment ( 33 ).…”
Section: Introductionmentioning
confidence: 99%
“…For the infected Artemia nauplii that received a delayed treatment, vB_VhaM_pir03 was unable to provide protection which suggested that the damage caused by vibriosis was irreversible similarly to the reported results of Diaz et al [ 84 ]. Phages are conventionally used in therapeutic purposes [ 27 ], however, for pathogens which cause irreversible damage, consideration may be given to use of phages as prophylaxis such as suggested by Silva et al and Zaczek et al [ 85 , 86 ].…”
Section: Discussionmentioning
confidence: 99%